2009
DOI: 10.1097/rct.0b013e318194b282
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Cor Triatriatum

Abstract: The fast scanning time and exceptional resolution of 64-slice multidetector computed tomography have expanded the role of imaging of congenital cardiac anomalies. These disorders involve complex cardiac configurations and require thorough evaluation of the entire cardiopulmonary system. Interactive interpretation of the multidetector computed tomographic volume with multiplanar postprocessing tools is essential for interpretation and display. This case report describes the utility of 3-dimensional volume rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been shown that surgeons highly value three‐dimensional tools in congenital heart disease due to their clear depiction of the anatomy and spatial relationships in addition to providing them with a familiar view of the situs 7,8 . Specifically when dealing with complex anatomy, 3‐D reconstructions are advantageous in surmounting the intrinsic limitations of cross‐sectional CT and MRI images as well as the planar views from echocardiography and conventional X‐ray angiography 9,10 . Eid et al 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that surgeons highly value three‐dimensional tools in congenital heart disease due to their clear depiction of the anatomy and spatial relationships in addition to providing them with a familiar view of the situs 7,8 . Specifically when dealing with complex anatomy, 3‐D reconstructions are advantageous in surmounting the intrinsic limitations of cross‐sectional CT and MRI images as well as the planar views from echocardiography and conventional X‐ray angiography 9,10 . Eid et al 6 .…”
Section: Discussionmentioning
confidence: 99%